Perceived Support and Emotional Well-being in First-Generation College Students - Pan, Yinghao; Zhang, Wei (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to explore the perceived sources of support and their influence on the emotional well-being of first-generation college students in China. This research employed a qualitative design grounded in a constructivist paradigm. Semi-structured interviews were conducted with 30 first-generation undergraduate students from various universities across China, selected through purposive sampling. Participants ranged in age from 18 to 24 and represented diverse academic disciplines and geographical backgrounds. Data collection continued until theoretical saturation was reached. All interviews were transcribed verbatim and analyzed thematically using NVivo software. The analysis focused on identifying recurring patterns and meanings associated with participants’ perceptions of support and emotional experiences. Thematic analysis revealed four overarching categories: academic and institutional support, family and social support, emotional challenges and coping, and identity and self-perception. Participants emphasized the importance of faculty accessibility, effective advising, peer academic collaboration, and resource availability in shaping their emotional security. Emotional encouragement from family, friendship networks, and campus social integration were also critical to well-being. Despite experiencing stress, self-doubt, and impostor feelings, many participants employed adaptive coping strategies such as journaling, exercise, and time management. A strong sense of belonging, academic confidence, and future orientation contributed positively to emotional resilience. The development of self-worth and meaning-making emerged as central to sustaining motivation and psychological well-being. Perceived support plays a vital role in fostering emotional well-being among first-generation college students. The findings underscore the need for culturally responsive, student-centered interventions that address academic, emotional, and identity-related needs. Institutions should enhance inclusive support systems, promote emotional regulation strategies, and validate the lived experiences of first-generation students to support their long-term success and mental health.